Alleviating effects of gut micro-ecologically regulatory treatments on mice with constipation - Zhao, Yueming; Liu, Qingjing; Hou, Yanmei; Zhao, Yiqing (Frontiers in Microbiology, 2022)
Treatments targeted for gut microbial regulation are newly developed strategies in constipation management. In this study, the alleviating effects of gut micro-ecologically regulatory treatments on constipation in mice were investigated. Male BALB/c mice were treated with loperamide to induce constipation, and then the corresponding intervention was administered in each group respectively. The results showed that administration of mixed probiotics (MP), a 5-fold dose of postbiotics (P5), both synbiotics (S and S2), as well as mixed probiotics and postbiotics (MPP) blend for 8 days shortened the time to the first black stool, raised fecal water content, promoted intestinal motility, and increased serum motilin level in loperamide-treated mice. Furthermore, these treatments altered gut microbial composition and metabolism of short-chain fatty acids (SCFA). Based on linear regression analysis, SCFA was positively correlated with serum motilin except for isobutyrate. It suggested gut microbial metabolites affected secretion of motilin to increase gastrointestinal movement and transportation function and thus improved pathological symptoms of mice with constipation. In conclusion, the alteration of gut micro-ecology is closely associated with gastrointestinal function, and it is an effective way to improve constipation via probiotic, prebiotic, and postbiotic treatment.